RESEARCH ON THE IMPROVEMENT OF THE INPUT SHAFT’S CONNECTION METHOD OF A AGITATOR - TAO Jun; ZHONG Ying; FEI LingZhi (Jixie qiangdu)
In order to solve the problem that a input shaft of the agitator 34-M-2001 in a polypropylene device produce cracks repeatedly in the same key groove after a certain period of time. Considering the installation space,economic,practical and other important factors. This paper proposed an improvement plan and demonstrate the feasibility of the program. According to the main reasons for the crack caused by the input shaft and the fact that it is not suitable to change the structural size of other positions of the shaft. An improved scheme of changing the key connection mode of the shaft to the keyless connection mode was proposed. The theoretical analysis method and finite element method were used to demonstrate the improvement scheme. The results showed that the keyless connection could significantly improve the safety factor of the shaft; It could also avoid the occurrence of stress concentration in the key groove,so the maximum stress value of the shaft under rated operating conditions was greatly reduced. If the program is used,the mechanical strength of the input shaft could be greatly increased,and the service life of the shaft could also be effectively improved. The above researches have a certain reference value in improving the mechanical performance and service life of the key transmission parts.